What Workers Say: Employee Voice in the Anglo-American Workplace - Spencer, Bruce (Labour / Le Travail, 2008)
The article reviews the book, "What Workers Say: Employee Voice in the Anglo-American Workplace," edited by Richard B. Freeman, Peter Boxall and Peter Haynes.
Keywords: BOOKS – Reviews; BOXALL; Peter; Employees; FREEMAN; Richard B.; HAYNES; Peter; Nonfiction; WHAT Workers Say: Employee Voice in the Anglo-American Workplace (Book)